PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DI SMK NEGERI 1 KEDUNGWUNI - Nur Fatwa; Sunarto Sunarto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to examine and analyze the role of organizational culture in moderating the influence of emotional intelligence and professional competence on teacher performance at SMKN 1 Kedungwuni, Pekalongan Regency. This study with a population of 101 people, namely all teachers of SMKN 1 Kedungwuni, Pekalongan Regency. The data collection technique used survey methods and the research instrument used a questionnaire with a Likert scale 5. The instrument test was carried out with validity tests through CFA, reliability tests, normality tests, heteroscedasticity tests, and model tests (F test, R-Square and sig). Test the hypothesis with quasi-regression analysis, interaction technique by looking at the sig value. The results showed that emotional intelligence had a positive effect on teacher performance, professional competence had a negative and significant effect on teacher performance, organizational culture had no significant effect on teacher performance, organizational culture moderated the influence of emotional intelligence and professional competence on teacher performance